Genome-wide identification and expression analyses of the LRR-RLK gene family in Actinidia chinensis - Li, Chang; Ma, Shengwei; Tian, Yulong; Zheng, Xiaojuan (Frontiers in Plant Science, 2025)
IntroductionMihoutao (Actinidia) has significant nutritional and economic value, with China leading the world in both cultivation area and production volume. However, bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa) poses a devastating threat to the Mihoutao industry, severely affecting yields. The most effective strategy to combat this disease is through the breeding of resistant varieties. The leucine-rich repeat receptor-like kinase (LRR-RLK) family, a major subclass of plant receptor-like kinases, plays crucial roles in plant growth and stress regulation. However, research on LRR-RLK genes in Mihoutao remains unexplored.MethodsIn this study, we performed a genome-wide identification of the LRR-RLK gene family in Actinidia chinensis cv. Hongyang (HY). Their phylogenetic relationships, gene structures, conserved motif, chromosomal location, gene duplication events and promoter cis-elements were analyzed. In addition, we analyzed the genes of the LRR-RLK gene family that respond to Psa infection based on transcriptomic data and verified their gene expression patterns by qRT-PCR.Results and discussionn this study, we identified and manually corrected LRR-RLK genes in two haplotypes of HY, resulting in a nonredundant set of 394 AcLRR-RLK genes. Phylogenetic analysis revealed that these AcLRR-RLK genes are classified into 21 subfamilies distributed across 29 chromosomes. Gene structure analysis revealed high diversity in the LRR domains of AcLRR-RLK genes, while the kinase domains were relatively conserved. Analysis of cis-acting elements further suggested the involvement of AcLRR-RLK genes in critical biological processes such as the light response, hormone response, growth and development, and biotic and abiotic stresses in HY. Furthermore, transcriptomic analysis across different tissues revealed that the majority of AcLRR-RLK genes play a role in five tissues: root, stem, leaf, flower, and fruit. Additionally, transcriptomic analysis under Psa infection indicated that, HY activated its defense response, with an increasing number of AcLRR-RLK genes responding to pathogen invasion. Among these genes, 48 AcLRR-RLK genes were identified as core genes responsive to Psa, and genes from subgroup XII may play a critical role in the defense mechanism against pathogen invasion. Our study provides an in-depth investigation into the characteristics and functions of the AcLRR-RLK gene family in A. chinensis, laying a molecular foundation for further disease-resistant and high quality breeding efforts.